2016
DOI: 10.1038/srep30265
|View full text |Cite
|
Sign up to set email alerts
|

High fat diet-induced TGF-β/Gbb signaling provokes insulin resistance through the tribbles expression

Abstract: Hyperglycemia, hyperlipidemia, and insulin resistance are hallmarks of obesity-induced type 2 diabetes, which is often caused by a high-fat diet (HFD). However, the molecular mechanisms underlying HFD-induced insulin resistance have not been elucidated in detail. In this study, we established a Drosophila model to investigate the molecular mechanisms of HFD-induced diabetes. HFD model flies recapitulate mammalian diabetic phenotypes including elevated triglyceride and circulating glucose levels, as well as ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 42 publications
1
57
0
Order By: Relevance
“…scw is required in early embryogenesis, where it acts in combination with dpp to specify dorsal cells fates ( Arora et al, 1994 ). gbb and dpp mutants have both distinct and overlapping phenotypes during and after embryonic development, suggesting that gbb and dpp are required together for proper signaling in some developmental contexts ( Goold and Davis, 2007 ; Haerry et al, 1998 ; Hong et al, 2016 ; Khalsa et al, 1998 ; Wharton et al, 1999 ). To assess whether gbb is involved in BMP signaling and Dpp expression in embryonic midgut and the generation of Pngl –/– phenotypes, we performed Dpp and pMad staining in gbb mutant embryos at stage 14, focusing on PS3 and PS7.…”
Section: Resultsmentioning
confidence: 99%
“…scw is required in early embryogenesis, where it acts in combination with dpp to specify dorsal cells fates ( Arora et al, 1994 ). gbb and dpp mutants have both distinct and overlapping phenotypes during and after embryonic development, suggesting that gbb and dpp are required together for proper signaling in some developmental contexts ( Goold and Davis, 2007 ; Haerry et al, 1998 ; Hong et al, 2016 ; Khalsa et al, 1998 ; Wharton et al, 1999 ). To assess whether gbb is involved in BMP signaling and Dpp expression in embryonic midgut and the generation of Pngl –/– phenotypes, we performed Dpp and pMad staining in gbb mutant embryos at stage 14, focusing on PS3 and PS7.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, consistent with the fact that both animal development and DR modulate molecule signaling in response to nutrient conditions, our results indicate that Wnt signaling controls DRinduced longevity as well as development. As many other developmental signaling pathways respond to nutrient status [50][51][52][53], it will be interesting to pursue whether they are also involved in DRinduced longevity.…”
Section: Discussionmentioning
confidence: 99%
“…gbb -/mutant animals show a phenotype that resembles the state of starvation, including reduced triacylglyceride storage and lower circulating carbohydrate levels (Ballard et al, 2010). It has previously been shown that overexpression of Gbb in the fatbody leads to higher levels of circulating carbohydrates and thus the opposite of a starvation-like phenotype (Hong et al, 2016a). Thus, to study their role in Tret1-1 regulation, we over-expressed Gbb or Dpp locally in the surface glial cells (9137-Gal4, perineurial and subperineurial glial cells) to avoid strong systemic impact that would counteract the effects of starvation.…”
Section: Glass-bottom Boat-mediated Tgf-β Signaling Induces Tret1-1 Ementioning
confidence: 99%